Bacterial Profile, Antibacterial Resistance Pattern, and Associated Factors from Women Attending Postnatal Health Service at University of Gondar Teaching Hospital, Northwest Ethiopia. (25th February 2018) - Bitew Kifilie, Abebaw; Dagnew, Mulat; Tegenie, Birhanemeskel; Yeshitela, Biruk; Howe, Rawleigh; Abate, Ebba
Abstract : Introduction. Surgical site infection is a vital cause of maternal mortality and morbidity, especially in resource-limited countries. The rise of antibiotic resistance bacterial infection poses a big threat to this vulnerable population. However, there is lack of studies around the study area. Objective. The purpose of this study was to identify bacterial profile, antibacterial resistance pattern, and associated factors among mothers attending postnatal care health service. Methods. Institutional based cross-sectional study was conducted on 107 study participants at University of Gondar Teaching Hospital from 1 January 2016 to 30 May 2016. Wound swab, aspirate, and biopsy were collected and performed for culture and drug resistance testing. Data were entered and analyzed by using SPSS version 20. Bivariate and multivariate logistic regression models were fitted to determine the associated factors for bacterial infection. Odds ratio (95% CI) was calculated to determine the strength of statistically significant associated factors. Result. Bacterial growth was confirmed in 90 (84.1%) of 107 study participants suspected to have surgical site infection. The predominant bacterial isolates were S. aureus (41.6%), E. coli (19.8%), K. pneumoniae (13.9%), coagulase negative Staphylococcus (12.9%), and Enterobacter spp. (4%). The majority of isolates were resistant to ampicillin, amoxicillin, and tetracycline but susceptible to ceftriaxone and amikacin. Multidrug-resistant bacteria species were isolated. Using a procedure such as cesarean section and episiotomy for delivery and premature rapture of membrane had strong association with bacterial infection. Conclusion. The high prevalence of bacterial profile and isolation of multidrug-resistant bacteria pose a big threat to postnatal mothers and their children. Factors such as cesarean section, episiotomy for delivery, and premature rapture of membrane were predictors for bacterial infection. Therefore, there should be done a continuous surveillance as well as rational use of antibiotics and a longitudinal study using phenotypic and genotypic methods will be done.